Hydrogen Embrittlement and Microstructure Characterization of 1500 MPa Martensitic Steel. Issue 10 (14th July 2022) - Si, Yu; Tang, Yuanshou; Xu, Zhengmeng; Yu, Shuoshuo; Zhou, Xin; Li, Kejian; Cao, Pengjun; Ma, Yilong
Abstract : The application of ultrahigh‐strength martensitic steel in automotive key parts can achieve automotive lightweight. However, the hydrogen embrittlement sensitivity of ultrahigh‐strength martensitic steel is widely concerned by the industry. This article compares the microstructure and the hydrogen brittleness resistance of two 1500 MPa martensitic steels. The grain boundary, the grain size, the martensitic lath, and the precipitate phase in martensitic steel are analyzed by electron backscatter diffraction and transmission electron microscope. The hydrogen desorption curves of the two steels are measured by thermal desorption analysis, and the phenomenon of hydrogen trapping in the materials is analyzed. A U‐bend test is used to compare the hydrogen embrittlement of these two samples. The results demonstrate that the thickness of the martensitic lath and the dislocation are directly related to the diffuse hydrogen concentration in the material. In addition, the Cu‐rich nanoparticles show a better hydrogen trapping effect, which is beneficial in improving the hydrogen embrittlement resistance of the material. Abstract : By increasing the thickness of martensitic lath, the dislocation density around the lath decreases, which greatly reduces the enrichment of hydrogen. At the same time, with the addition of trace Cu element, the precipitated Cu‐rich nanoparticles play the role of hydrogen trapping and disperse the diffuse hydrogen in the material, which shows better hydrogen brittleness resistance.